(untitled) (Research, Society and Development, 2022)
Newborn screening test is a laboratory exam that allows identifying genetic, congenital and infectious conditions before symptoms appear. The aim of this study was to investigate the knowledge of pregnant women, puerperum and health professionals about the foot test and the diseases detected by it. The cross-sectional observational research was developed in the Basic Health Units of Diamantina-MG with 127 people. Most of the interviewees had some information about the foot test. However, it was observed that a significant portion of pregnant women and puerperum women did not know their importance and, on average, 52% of them did not receive information about the prenatal test. Only 18% of the health professionals were able to describe which diseases are tracked by the test and none of the pregnant women and puerperum could mention all the diseases. More than 95% of the research participants reported the need for guidance on the subject, with emphasis on the types of diseases screening. Thus, it can be concluded that the knowledge of the evaluated public proved to be superficial, and showed the need for training and educational actions, both for professionals and mothers, so that they have a broad knowledge of the exam.